(untitled) (Scientific journal of the Fergana State University, 2024)
In recent decades in linguistics are increasingly used terms “cognitive”, “cognitive science”. Some researchers writing about the emergence of a new, “cognitive” paradigm in linguistics. According to researchers, the anthropocentric approach to language, studying language as inextricably linked with human thinking and consciousness, has laid the groundwork for the emergence of new directions in modern linguistics - cognitive linguistics and linguaculturology. The history of the emergence of cognitive linguistics, which has become a leading field in 21st century linguistics, is associated with the theory of American linguist Noam Chomsky. Famous Russian linguist Maslova in her book named “Cognitive Linguistics” defines cognitivism “the direction of science, which is the object of study of the human mind, thinking and those mental processes and conditions that are associated with them”. By interpretation of Demyankova and Kubryakova, cognitive linguistics studies language as a cognitive mechanism that plays a role in encoding and transforming information. Reflections about the participation of language in knowledge of the world can be found in the works of thinkers of different times and peoples from antiquity to the present day.